Dual Input Interleaved Three-Phase Rectifier In Discontinuous Conduction Mode For Application In Small Wind Turbines - Guilherme M. Todys; Luís P. Custódio; Alceu A. Badin; Amauri A. Assef; Roger Gules; Delvanei G. Bandeira Jr.; Eduardo F. R. Romaneli; Daniel F. Cortez (Eletrônica de Potência)
This paper presents a high-gain three-phase interleaved rectifier operating in DCM, with dual input, for application in small wind generators. The two input diode bridges promote the sharing of the current, resulting in a significant reduction of the converter's current stresses when compared to previous topologies. A theoretical analysis of the proposed converter was performed, followed by a simulation study, and experimental tests with a physical prototype. The simulations compared the proposed three-phase rectifier with three other three-phase topologies, demonstrating its operation with significantly reduced current stresses and smaller input inductors. The experiments compared the operation of the converter when working with a three-phase power supply, and a wind turbine in association with an MPPT method using the Perturb and Observe P&O technique. For an output power of 1 kW, on a 400 V DC bus and an input RMS line voltage of 114 V, the structure's obtained efficiency was higher than 95%. Furthermore, the experimental results confirmed that the rectifier operates with sinusoidal input currents, low current ripple, and high power factor for all the tested scenarios.